Target tumor microenvironment by innate T cells - Li, Yan-Ruide; Wilson, Matthew; Yang, Lili (Frontiers in Immunology, 2022)
The immunosuppressive tumor microenvironment (TME) remains one of the most prevailing barriers obstructing the implementation of effective immunotherapy against solid-state cancers. Eminently composed of immunosuppressive tumor associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) among others, the TME attenuates the effects of immune checkpoint blockade and adoptive cell therapies, mandating a novel therapy capable of TME remediation. In this review we explore the potential of three innate-like T cell subsets, invariant natural killer T (iNKT), mucosal-associated invariant T (MAIT) cells, and gamma delta T (γδT) cells, that display an intrinsic anti-TAM/MDSC capacity. Exhibiting both innate and adaptive properties, innate-like T cell types express a subset-specific TCR with distinct recombination, morphology, and target cell recognition, further supplemented by a variety of NK activating receptors. Both NK activating receptor and TCR activation result in effector cell cytotoxicity against targeted immunosuppressive cells for TME remediation. In addition, innate-like T cells showcase moderate levels of tumor cell killing, providing dual antitumor and anti-TAM/MDSC function. This latent antitumor capacity can be further bolstered by chimeric antigen receptor (CAR) engineering for recognition of tumor specific antigens to enhance antitumor targeting. In contrast with established CAR-T cell therapies, adoption of these innate-like cell types provides an enhanced safety profile without the risk of graft versus host disease (GvHD), due to their non-recognition of mismatched major histocompatibility complex (MHC) molecules, for use as widely accessible, allogeneic “off-the-shelf” cancer immunotherapy.